Validity and reliability of a global positioning system to assess 20 m sprint performance in soccer players - Yanci, J.; Calleja-Gonzalez, J.; Cámara, J.; Mejuto, G.; San Román, J.; Los Arcos, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
The aims of the present study were (1) to analyze the association between the time score obtained by a global positioning system device at a frequency of 10 Hz and by timing gates and (2) to assess intrarater reliability and agreement of these two methods in a 20 m straight sprint test. Twelve amateur soccer players (age: 21.08 ± 1.57 years) gave their voluntary consent to take part in this study. Each player performed five repetitions of a 20?m sprint test in each of the two test sessions. The start of the sprint for the global positioning system device was determined by a continuous increase in speed from below (0-0.1 km/h). No significant relationship (r = 0.118, p > 0.05) between 20 m straight sprint times measured by the timing gates and the global positioning system was found. The test-retest intra-class correlation coefficient obtained from the measurement of sprint times with the global positioning system device was small (r = 0.118, p > 0.05). The continuous increase in speed from below (0-0.1 km/h) seems not to be a precise way to evaluate the sprint time by a global positioning system device in a 20 m straight sprint test.